Rapid NMR Assignments of Proteins by Using Optimized Combinatorial Selective Unlabeling. (8th January 2016) - Dubey, Abhinav; Kadumuri, Rajashekar Varma; Jaipuria, Garima; Vadrevu, Ramakrishna; Atreya, Hanudatta S.
Abstract: A new approach for rapid resonance assignments in proteins based on amino acid selective unlabeling is presented. The method involves choosing a set of multiple amino acid types for selective unlabeling and identifying specific tripeptides surrounding the labeled residues from specific 2D NMR spectra in a combinatorial manner. The methodology directly yields sequence specific assignments, without requiring a contiguously stretch of amino acid residues to be linked, and is applicable to deuterated proteins. We show that a 2D [ 15 N, 1 H] HSQC spectrum with two 2D spectra can result in ∼50 % assignments. The methodology was applied to two proteins: an intrinsically disordered protein (12 kDa) and the 29 kDa (268 residue) α‐subunit of Escherichia coli tryptophan synthase, which presents a challenging case with spectral overlaps and missing peaks. The method can augment existing approaches and will be useful for applications such as identifying active‐site residues involved in ligand binding, phosphorylation, or protein–protein interactions, even prior to complete resonance assignments. Abstract : Removing labels : A new approach for rapid NMR assignments of proteins based on amino acid selective unlabeling is described. The method involves choosing optimal amino acids for selective unlabeling and identifying tripeptides with 2D NMR spectra in a combinatorial manner. With this approach, ∼50 % sequence specific assignments can be obtained directly.